Religious education in Italian public schools: what room for Islam? (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Introduction - 2. Religious education in Italian public schools: general framework - 3. Religious education in public schools: the situation of Islam - 3.1. Some data about the Islamic presence in Italy - 3.2. Religious education and Islam - 4. The religious education in plural Italy: challenges and gaps - 5 - Muslims at school and Religious Education: which solutions? - 5.1 Alternative 1: private schools - 5.2 Alternative 1-bis: Homeschooling - 5.3 Alternative 2: introduction of lessons about religion - 5.4 Alternative 3: Muslim pupils and their participation in the Catholic religion lessons - 6. Conclusions: challenges, problems and future perspectives.